The Relationship Between Maternal Knowledge Level About Exclusive Breastfeeding and Breastfeeding Success in the Area of Birem Bayeun Health Center Birem Bayeun District East Aceh Regency - Sabrina; Miftahul Jannah; Nurdiniah; Nenti Andriani; Nurlinda (Journal Public Health and Clinical Science, 2026)
Exclusive breast milk is the best source of nutrition for babies aged 0–6 months because it contains complete nutrients and antibodies that are essential for growth and immunity. However, the scope of exclusive breastfeeding is still not optimal. One of the factors that affect the success of exclusive breastfeeding is the mother's level of knowledge. To determine the relationship between the level of knowledge of mothers about exclusive breastfeeding and the success of breastfeeding in the working area of the Birem Bayeun Health Center, Birem Bayeun District, East Aceh Regency. This study used a quantitative method with a cross sectional design. The population in this study is all mothers who have 50 babies aged 0–6 months, with a sampling technique using total sampling. Data collection was carried out using a questionnaire and analyzed with the Chi-Square test at a confidence level of 95%. The results showed that most of the respondents had a good level of knowledge as many as 22 people (44%). Most mothers had success in exclusive breastfeeding in the good category as many as 28 people (56%). The results of the Chi-Square test showed a p-value of 0.000 (p < 0.05). Conclusion: There was a significant relationship between the level of maternal knowledge about exclusive breastfeeding and the success of breastfeeding in the working area of the Birem Bayeun Health Center, Birem Bayeun District, East Aceh Regency. It is hoped that health workers can increase education and counseling to pregnant women and lactating mothers about the importance of exclusive breastfeeding to increase the success of breastfeeding.